Synthesis and Spectral Characterization of 4-Methoxybenzoylmethylenetri-p-tolylphosphorane and It’s Reaction with Mercury(II) Halides - JAVAD SABOUNCHEI, SEYYED; JODAIAN, VIDA (Asian Journal of Chemistry, 2010)
The reaction of the 4-methoxybenzoylmethylenetri-ptolylphosphorane (CH3C6H4)3PCHCOC6H4OCH3) (MBPTY) with mercury(II) halide in equimolar ratios using methanol as solvent have yielded [(MBPTY)·HgCl2]2 (1), [(MBPTY)·HgBr2]2 (2), [(MBPTY)·HgI2]2 (3). IR, 1H, 13C and 31P NMR together with microanalysis data of the products were obtained. Analytical data indicate a 1:1 stoichiometry between the ylide and Hg(II) halide in each of the three products.